study of the main cultural goods immaterial of the Historic Center of Lima - Vizcardo Otazo, Daniel (2009)
Cultures that are for the Historic Center of Lima were influenced by other cultural groups in various historical processes of both pre-Hispanic and Hispanic. In the study of this research highlight the identity and appreciation of our cultural heritage of the historic center of Lima in their intangible assets, which were accentuated population groups in the Historic Center of Lima, with different customs, traditions, beliefs, customs, dances , in administrative, religious cults, lifestyles, among others. During the Hispanic period the Spanish chose the lands of the manor or Itchma chiefdom, the chief Taulichusco to establish their dominion and to shed all the intangibles they brought from Spain and merged with the Lima Prehispdnica, including We Fight cock-Games invite, the covered, bullfights, carnivals, etc..